Quality-in-use app evaluation: case of a recruitment app for Portuguese SMEs - Barreto, D. M.; Alturas, B. (Journal of Information Systems Engineering and Management, 2018)
E-Recruitment, a term that refers to online recruitment, has been increasingly adopted by companies that are prone to changes and ready to the constant evolution of society. Thus, this study aims to evaluate the impact of a recruitment application in Portugal. This application was developed to meet the needs of candidates and employers, and its evaluation is made in terms of quality-in-use by both parties, small and medium-sized companies in Portugal and potential job offers applicants. To achieve the results related to the defined objective, managers from six companies were interviewed, producing a qualitative evaluation of the application, accompanied by a survey to achieve its quantitative evaluation (3.36 in 4 points). Simultaneously, a quantitative study was carried out among the candidates for evaluation of the mobile application, 3.67 points out of 4 possible. Thus, it was verified that the application developed is suitable for candidates. However, despite the positive evaluation, recruiters point to improvements in the company module.